2020
DOI: 10.1186/s12891-020-03430-y
|View full text |Cite
|
Sign up to set email alerts
|

High rate of unexpected positive cultures in presumed aseptic revision of stiff shoulders after proximal humerus osteosynthesis

Abstract: Background: The aim of this study was to investigate the prevalence of positive microbiology samples after osteosynthesis of proximal humerus fractures at the time of revision surgery and evaluate clinical characteristics of patients with positive culture results. Methods: All patients, who underwent revision surgery after locked platting, medullary nailing or screw osteosynthesis of proximal humeral fractures between April 2013 and July 2018 were retrospectively evaluated. Patients with acute postoperative in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Then again, Akgun et al reported a 50% rate of positive cultures in a presumed aseptic revision of proximal humerus osteosynthesis. 22,23 Regarding hip surgery, Hemmann et al 16 conducted a study to analyze the safety of a single-stage revision of Total Hip Arthroplasty (THA) in failed fixations of PFFs. They found that 10% of the cases presented with positive microbiological tests despite a lack of clinical signs of infection preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Then again, Akgun et al reported a 50% rate of positive cultures in a presumed aseptic revision of proximal humerus osteosynthesis. 22,23 Regarding hip surgery, Hemmann et al 16 conducted a study to analyze the safety of a single-stage revision of Total Hip Arthroplasty (THA) in failed fixations of PFFs. They found that 10% of the cases presented with positive microbiological tests despite a lack of clinical signs of infection preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Akgün et al showed a 50% rate of unexpected positive cultures for Propionibacterium acnes in patients undergoing surgery for post-surgical stiffness after ORIF. They suggested routine evaluation in all patients undergoing revision surgery after ORIF ( 15 ).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Thus, it makes sense that Cutibacterium spp. are not only common pathogens in postoperative infections after shoulder arthroscopy and arthroplasty [22][23][24][25] , but also in FRI after fracture surgery in the proximal humerus 26 .…”
Section: Pathogensmentioning
confidence: 99%